Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1651-2227.2008.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier use: What makes mothers change their mind?

Abstract: About one third of mothers had changed their mind about pacifier use, either because of rejection by the infant or the need of settling. Breastfeeding mothers require more and better information concerning the appropriate time of pacifier onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 32 publications
2
20
1
4
Order By: Relevance
“…Sertório & Silva 3 comentam que as mães que não amamentam reconhecem a necessidade da sucção independente da alimentação e, ao oferecerem a chupeta, percebem que "as crianças acalmam". A esse respeito, Pansy et al 25 , avaliando 174 binômios (mães e filhos) austríacos através de um questionário semiestruturado, verificaram que 31% das mães tinham mudado de opinião quanto ao uso da chupeta até os bebês completarem 5 meses. Segundo os autores, logo após o nascimento, a maioria das mães (135/174) pretendia oferecer a chupeta aos filhos, e apenas 39 (das 174) não tinham essa intenção.…”
Section: Psicologiaunclassified
“…Sertório & Silva 3 comentam que as mães que não amamentam reconhecem a necessidade da sucção independente da alimentação e, ao oferecerem a chupeta, percebem que "as crianças acalmam". A esse respeito, Pansy et al 25 , avaliando 174 binômios (mães e filhos) austríacos através de um questionário semiestruturado, verificaram que 31% das mães tinham mudado de opinião quanto ao uso da chupeta até os bebês completarem 5 meses. Segundo os autores, logo após o nascimento, a maioria das mães (135/174) pretendia oferecer a chupeta aos filhos, e apenas 39 (das 174) não tinham essa intenção.…”
Section: Psicologiaunclassified
“…If this practice is begun before breastfeeding is established it can lead to weaning, both because of nipple confusion and also because the lack of stimulus leads to a reduction in milk production. Pacifiers were generally given during infants' first month of life and particularly during the first week of life, which has also been observed in other studies (14,21) . Howard et al (22) observed that pacifier use was correlated both with exclusive breastfeeding duration and with breastfeeding duration.…”
Section: Intended To Use a Pacifier (N=390)mentioning
confidence: 67%
“…Unlike recommendations against smoking and non-supine sleeping positions; the pacifier recommendation has been controversial (Fleming, Blair & McKenna, 2006). Recommendations to use a pacifier compete with some mothers’ and dentists’ fears that pacifiers will harm infants’ developing mandibles, (Pansy et al, 2008; Vazquez-Nava et al, 2006; Warren et al, 2005) impair breastfeeding, (Howard et al, 2003; Scott et al, 2006) or increase otitis media (Uhari, Mäntysaari & Niemelä, 1996). …”
Section: Discussionmentioning
confidence: 99%